Granulomatous Lymphocytic Interstitial Lung Disease in Infancy. Issue 1 (2014) - Adeleye, Adetayo; Kelly, Margaret M; Wright, Nicola AM; Yu, Weiming; Anselmo, Mark A
Abstract : The authors report a case involving a child with chronic respiratory symptoms, who did not respond to conventional treatment. Low serum immunoglobin levels and pathological findings on lung biopsy revealed an unusual diagnosis for his age group. A specific treatment led to clinical improvement.